Secretarial management as a theoretical proposal: developing the state of issue - Barros, Conceição de Maria Pinheiro; Silva, Joelma Soares da; Sousa, Elaine Freitas de; Silva, Francisco Edson Rodrigues da (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
Secretarial management is a recurring subject in national Executive Secretariat studies but still lacks scientific evidence. This study aims to analyze Brazilian researches’ contributions to consolidate Secretarial Management as a theoretical proposal. Methodologically, the State of Issue research was used, which is based on Nóbrega-Therrien and Therrien (2010). The contents of one doctoral dissertation and of seventeen national articles were analyzed. As an outcome, few studies on the subject were identified, which is an evidence of gaps related to the consolidation of the knowledge area and to the establishment not only of its object of study but also of a theoretical-methodological framework. The researches indicate how interdisciplinary the area is, since it keeps a dialogue mainly with management studies. The State of Issue provided a broad vision of: the current state of knowledge, the researchers’ main approaches and their theoretical and empirical support basis.